S.T.O.N.E. Score, Guy's Score, and CROES Nomogram in Predicting Stone Clearance following Percutaneous Nephrolithotomy - Timilsina, Bhusan Raj; Pradhan, Sulav; Sah, Nirmal Prasad; Thapa, Ganesh; KC, Sudeep Raj (Journal of Bharatpur Hospital, 2025)
Background Percutaneous Nephrolithotomy (PCNL) is the standard treatment for large renal calculi. Several scoring systems have been developed to preoperatively predict its success. This study aims to compare the predictive accuracy of the Guy's Stone Score (GSS), S.T.O.N.E. nephrolithometry, and the Clinical Research Office of the Endourological Society (CROES) nomogram for stone-free status after PCNL. MethodsA single-center, cross-sectional study was conducted from February 2021 to August 2022, including 75 patients who underwent PCNL. Preoperative variables were used to calculate the three scores. Stone-free status was defined as residual fragments